2009
DOI: 10.1111/j.1468-2419.2008.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of vocational training to employment, job‐related skills and productivity: evidence from Madeira

Abstract: In this paper, we analyse the transition to the labor market of participants in vocational training in Madeira in Portugal. The analysis is in two stages. First, we investigate how the employment status at different dates (1 month, 1 year, and 2 years after the completion of the training program) depends on relevant variables, such as age, gender, education and the content and duration of the training. Second, we use individuals' selfassessment of the effectiveness of the training program along three dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 36 publications
(37 reference statements)
2
21
0
Order By: Relevance
“…Educated individuals face far better employment prospects after an IVT than noneducated persons, seen as having a lower secondary, upper secondary and higher education increases the employment probability by 4.4%, 13% and 16%, respectively. This finding is consistent with the results of similar analysis, but based on different data, such as Budrı´a and Telhado-Pereira (2008). Being out of the labour market for a certain time negatively influences employment prospects after training, Extending training by a month increases employment probability by 4.3%.…”
Section: Resultssupporting
confidence: 94%
“…Educated individuals face far better employment prospects after an IVT than noneducated persons, seen as having a lower secondary, upper secondary and higher education increases the employment probability by 4.4%, 13% and 16%, respectively. This finding is consistent with the results of similar analysis, but based on different data, such as Budrı´a and Telhado-Pereira (2008). Being out of the labour market for a certain time negatively influences employment prospects after training, Extending training by a month increases employment probability by 4.3%.…”
Section: Resultssupporting
confidence: 94%
“…Later studies have confirmed this assessment. Budría and Telhado‐Pereira, (2009), using a logit model 6 on individual data for Madeira in Portugal, found that vocational training increases the probability of employment, in particular in the long run (2 years after the completion of the training programme). However, they also found that the effect is stronger with higher previous education, and in particular, that the effects are very strong for a person with a tertiary education prior to the training programme.…”
Section: A Remedy For Youth Unemployment?mentioning
confidence: 99%
“…In relation to developing countries, bilateral aid agencies, the World Bank and United Nations Educational, Scientific and Cultural Organization (UNESCO) advocate vocational education to reduce poverty, promote economic growth and increase competitiveness (Comyn & Barnaart, 2010). In a European context, it is seen as a major tool in the transformation of the European economy (Bordeaux Communiqué, 2008), and there are numerous examples of presumed effects in countries, regions and specific sectors of the economy (Baum, 2002; Budría and Telhado‐Pereira 2009; Mupimpila & Narayana, 2009; Spielhofer & Sims, 2004). There are two major reasons for this.…”
Section: Introductionmentioning
confidence: 99%
“…Vocational Education and training (VET) can be broadly interpreted as the development of ways of learning and the acquisition of attitudes that facilitate success at the workplace [44]. The aim of VET is to contribute to equity and access to training, and social responsibility by stimulating competitiveness and entrepreneurship to realise life-long learning concepts [41] VET plays an important role in supplying skills requisite for improved workers' productivity, economic competitiveness, occupational integration, raising income levels and expanding opportunities for employment [11,15]. In addition, formal education and work experience in the formal business sectors enables employers and business owners to improve methods of production, enhance product quality, convey quality information to the users, identify markets, and manage human and other resources, all of which offer students a competitive edge [54].…”
Section: Introductionmentioning
confidence: 99%